1998
DOI: 10.3109/10826089809059323
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Program of Research on Drug Use and Crime

Abstract: This paper describes the major findings emanating from a long-term research program conducted in Baltimore, Maryland, on the drugs-crime relationship. It is the compilation of experiences, studies, and findings related to the research career of David N. Nurco, D.S.W., and his colleagues. Covering a period of over 30 years, the program of research, described in the report from the personal perspective of Dr. Nurco, has moved from the study of the nature and correlates of narcotic drug use to the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 22 publications
5
74
0
1
Order By: Relevance
“…The 197 participants resembled previous samples of incarcerated offenders from large American cities with histories of heroin addiction regarding the following characteristics: disproportionately African American (Inciardi et al, 1998;Inciardi, Martin, Butzin, Hooper, & Harrison, 1997;Kinlock et al, 2002;Kinlock et al, 2003); low educational attainment compared to the general population (Inciardi et al, 1997;Kinlock et al, 2002); early onset of both drug use and crime during the teenage years, with marijuana use preceding use of heroin and cocaine (Chaiken & Chaiken, 1990;Kinlock et al, 2002;Nurco, 1998); more involvement with incarceration than with drug abuse treatment (Inciardi et al, 1998;Kinlock et al, 2002); and rapid relapse to heroin addiction following prior incarcerations (Maddux & Desmond, 1981;Kinlock et al, 2002;Nurco et al, 1991). However, the sample was approximately 10 to 15 years older than the above-mentioned previous samples of incarcerated offenders and generally about 2 to 3 years older at first heroin use than other samples of heroin-dependent males (Chaiken & Chaiken, 1990;Kinlock et al, 2003), although similar in age of heroin onset to participants in the investigators' previous study of opioid-agonist maintenance (Kinlock et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 197 participants resembled previous samples of incarcerated offenders from large American cities with histories of heroin addiction regarding the following characteristics: disproportionately African American (Inciardi et al, 1998;Inciardi, Martin, Butzin, Hooper, & Harrison, 1997;Kinlock et al, 2002;Kinlock et al, 2003); low educational attainment compared to the general population (Inciardi et al, 1997;Kinlock et al, 2002); early onset of both drug use and crime during the teenage years, with marijuana use preceding use of heroin and cocaine (Chaiken & Chaiken, 1990;Kinlock et al, 2002;Nurco, 1998); more involvement with incarceration than with drug abuse treatment (Inciardi et al, 1998;Kinlock et al, 2002); and rapid relapse to heroin addiction following prior incarcerations (Maddux & Desmond, 1981;Kinlock et al, 2002;Nurco et al, 1991). However, the sample was approximately 10 to 15 years older than the above-mentioned previous samples of incarcerated offenders and generally about 2 to 3 years older at first heroin use than other samples of heroin-dependent males (Chaiken & Chaiken, 1990;Kinlock et al, 2003), although similar in age of heroin onset to participants in the investigators' previous study of opioid-agonist maintenance (Kinlock et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies have consistently found that rapid relapse to opioid (principally, heroin) addiction following incarceration is a continuing problem. Several reports indicate that readdiction is typically well established within 90 days of release (Office of National Drug Control Policy, 1999;Stewart, 1995;Wexler, Lipton, & Johnson;1988), whereas other reports have found that most incarceration episodes are followed by relapse as early as 1 month after release (Kinlock, Battjes, & Schwartz, 2002; Maddux & Desmond, 1981;Nurco, Hanlon, & Kinlock, 1991).In addition to its high prevalence, readdiction to heroin is accompanied by increased criminal activity (Chaiken & Chaiken, 1990;Kinlock, O'Grady, & Hanlon, 2003;Nurco, 1998), disproportionately high risk of HIV infection (Chitwood, Comerford, & Weatherby, 1998; Correspondence concerning this article should be addressed to Timothy W. Kinlock Inciardi, McBride, & Surratt, 1998), Hepatitis B and C infections (Edlin, 2002;Fuller, Vlahov, Safeian, Ompad, & Strathdee, 1999;Hagan et al, 2002) (Inciardi et al, 1998;Mark et al, 2001), and impaired parenting (Keller, Catalano, Haggerty, & Fleming, 2002). Thus, the development and implementation of effective drug abuse treatment strategies for incarcerated offenders with heroin-addiction histories is urgently needed, not only for such individuals' rehabilitation but also for their survival and for the safety and welfare of the public (Kinlock et al, 2002;Rich, Boutwell, et al, 2005; SmithRohrberg, Bruce, & Altice, 2004).…”
mentioning
confidence: 99%
“…Specifically, the onset of a substance use disorder is associated with a higher propensity for more severe forms of substance use, including polydrug use (American Psychiatric Association, 2000; Ellickson et al, 2004;Newcomb et al, 2001) and use of "hard drugs" (e.g., cocaine and heroin) (Chaiken and Chaiken, 1990;Ellickson et al, 2004;Morral et al, 2002). Severe forms of substance use, in turn, are associated with impulse control problems (Cunningham, 2004), and may motivate participation in drug selling and other crimes in order to obtain drugs or money to purchase drugs (Fagan, 1990;Nurco, 1998).…”
Section: Substance Use Disorders and Incarceration Riskmentioning
confidence: 99%
“…However, evidence on the association of onset and course of substance use disorders with the risk of involvement with criminal justice systems (i.e., contact with law enforcement, judicial, and corrections systems that is related to one's own alleged or established violations of law) is scarce. Many research studies provide evidence that substance use and involvement in crime frequently co-occur in adolescence and early adulthood (Nurco, 1998;Hays and Ellickson, 1996;White and Gorman, 2000;McBride et al, 2003;Gordon et al, 2004). Recent studies of longitudinal data from a non-U.S. cohort provide evidence that heavy use of alcohol and marijuana in adolescence is positively related to later criminal justice system involvement (Fergusson and Horwood, 2000;Fergusson, Horwood, and SwainCampbell, 2002;.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34] Many illicit opioid users generate revenue for their considerable drug expenditures through criminal activities and/or social support sources, thus also incurring major societal cost. 35,36 A recent cost-of-illness analysis of a local sample of illicit opioid users in Toronto found a social cost burden of $45,000 per untreated user/year. 20 In Canada and globally, methadone maintenance treatment (MMT) is currently the main treatment response for opioid dependence.…”
Section: Introductionmentioning
confidence: 99%